Financial Ratio Analysis to Assess Financial Performance of the Hotel Industry - supatmi, supatmi (International Journal of Social Science and Business, 2021)
The aim of this research was to analyze financial ratio to assess the financial performance of hotel industry in 2015-2018. Research sample were 12 companies of 35 hotel industries that were listed in Indonesian Stock Exchange in 2015-2018. Analysis tool used in this research were liquidity ratio, profitability ratio, activity ratio, leverage ratio, and operational ratio. Research result showed good ratios; they were liquidity ratio that was indicated by current ratio, profitability ratio that was pointed by net profit margin, return on asset, and return on equity, also paid occupancy percentage on activity ratio. While the not good ratio, which was activity ratio was pointed by total asset turnover, then leverage ratio by equity multiplier, debt to asset ratio, and debt to equity ratio, also operational ratio which was showed through average room rate and food and beverage cost.